DETERMINAN KONSERVATISME AKUNTANSI PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BEI - Abdil Alfaresi; Muhammad Fuad; Nasrul Kahfi Lubis; Meutia, Tuti (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2024)
This study intends to discuss the effect of capital intensity, dividend payout ratio and financial distress on accounting conservatism of energy sector companies listed on the IDX. This research was conducted at Energy Sector Companies Listed on the Indonesia Stock Exchange (IDX) using secondary data obtained from published company financial reports. The data analysis method used is multiple linear regression and uses statistical tools, namely SPSS software. The results of this study indicate that Capital Intensity has a significant effect on Accounting Conservatism, Dividend Payout Ratio has a significant effect on Accounting Conservatism, Financial Distress has no significant effect on Accounting Conservatism and Capital Intensity, Dividend Payout Ratio and Financial Distress simultaneously have a significant effect on Accounting Conservatism.